MANAGEMENT OF COMMUNITY BASED TOURISM (CBT) IN THE SIHONONGAN TOURISM VILLAGE, PARANGINAN DISTRICT, HUMBANG HASUNDUTAN REGENCY - Muhammad Zulfan (Jurnal Ilmiah Akomodasi Agung, 2023)
This resear chaim stop rovidean overview of Community Based Tourism (CBT) management in the Sihonongan Tourism Village, Parangnan District, Humbang Hasundutan District. This research uses a qualitative approach with a case study method. Data wascollected through in-depth interviews with CBT managers and local communities, as well asfield observations. The results showed that CBT management in Sihonongan Tourism Villagewas carried out in a participatory manner by involving the community in decision-making.CBT managers and the community work together to develop tourism products based on culture and the natural surroundings. Infrastructure development is carriedout by considering environmental and social impacts and involving local workers. Promotion and marketing are carried out by utilizing social media and collaboration networks with travelagents. CBT financial management is carried out transparently by involving thecommunity in fund management and profit sharing. Training and development of humanresources are carried out regularly to improve the quality of services and management of thetourism business. However, there are still several challenges faced in managing CBT in Sihonongan Tourism Village, such as infrastructure problems that still need to be improved,a lack of public understanding of the tourism business, and the need to improve promotion andmarketing. The conclusion is that CBT management in the Sihonongan Tourism Village iscarried out in a participatory manner by involving the community in the decision-making andmanagement of the tourism business. Development of cultural and natural-based tourismproducts, promotion, and marketing through social media, transparent financial management,and human resource training and development are some of the things being done to enhance CBT development. Challenges still exist, but with cooperation between CBT managers and local communities, they can be over come to achieve the goal of sustainable tourism development.